KINETIN INFUSION THROUGH AN ORGANIC SOLVENT AS A MEANS OF REDUCING SOYBEAN SEED DETERIORATION DURING HIGH-TEMPERATURE STORAGE - Marwanto Marwanto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2005)
Soybean seeds deteriorate rapidly when stored under unfavorable conditions and kinetin infusion prior to storage may reduce the rate of seed deterioration. To answer this hypothesis, seeds of three cultivars of soybeans with black seed coat color were permeated for four hours at a room temperature with hormone kinetin at a concentration of 1.0 mM dissolved in acetone before storage at 350C for up to six months in Agronomy Laboratory on July 2000, and their germination, accelerated aging germination and germination speed were compared with those of untreated seeds stored under the same conditions. The treatments were arranged in a split split plot design with three replications. Seeds that had been infused with kinetin prior to storage germinated to a high final percentage (from 98 to 83%) up to four months of storage, maintained a high accelerated aging germination (from 97 to 65%) up to four months of storage and retained a high speed of germination throughout the storage period. By contrast, untreated seeds showed a rapid decline in the three seed quality indicators, and by six months of storage their germination was already less than 30% and their accelerated aging germination declined to less than 20%. The promotive effects of kinetin infusion on reducing the rate of deterioration of soybean seeds were apparently dependent of the cultivar. Among the three cultivars, seeds of Cikuray lost their germination, accelerated aging germination and speed of germination at a slower rate than those of Merapi and Kalitur irrespective of kinetin infusion treatment and storage period. Therefore, it is evident that kinetin infusion prior to storage, in addition to the acceleration of germination, resulted in a delay of soybean seed deterioration.